Pengaruh Penggunaan Financial Technology, Gaya Hidup dan Pendapatan Orang Tua Terhadap Perilaku Keuangan Mahasiswa - Wulan Dwi Putri; Amy Fontanella; Desi Handayani (Akuntansi dan Manajemen, 2023)
This study aims to examine the effect of using financial technology, lifestyle and parental income on student financials behavior. This research was conducted on students of the Accounting Department of the DIII and DIV Study Programs of Accounting at the Padang State Polytechnic. This research method was conducted with a quantitative method using a questionnaire as a research instrument and measured using liket scale. The results of this study indicate that using financial technology affects students' financials behavior, meaning that if someone uses financial technology, it will impact on how he manages his finances. Lifestyle variables are not proven to have an effect on students' financials behavior while parental income has a negative effect on students' financial behavior. This result shows that the higher the income level of parents will reduce the ability of students' financial management behavior. The findings of this study imply that financial technology play an importants role in financials behaviour, the higher the use of financial technology, the better the financial behavior of students. Apart from being a transaction tool in daily activities, fintech can also support student financial activities such as saving, investing for future needs, making necessary payments and supporting business activities that can support income so that they can manage finances properly and precisely.